Crossing and Controlling Borders Immigration Policies and Their Impact on Migrants' Journeys - Baumann, Mechthild
This volume highlights the impact of border controls on migrants' journeys in two major areas of immigration: the European Union and the United States of America. In order to show the linkages between border control policies and migratory practices, the book combines empirical insights from ethnography with approaches from political science. Describing migrants' realities reveals that the impact of border control policies goes beyond the actual border area affecting many lives and states
Keywords: Europäische Union; Emigration and immigration; POLITICAL SCIENCE; Politische Kontrolle; Grenzpolizeiliche Kontrolle; Einwanderung; USA; European Union countries / Emigration and immigration / Government policy; United States / Emigration and immigration / Government policy; Pays de l'Union européenne / Émigration et immigration / Politique gouvernementale; European Union countries; United States; Electronic books; Aufsatzsammlung